Analisis Visualisasi Film Menjelang Magrib Mengenai Tradisi Pasung Pada Orang Dalam Gangguan Jiwa Menggunakan Teori Semiotika - Rahmat Ramadhan; Jupriani Jupriani (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this research is to analyze the visual signs in Menjelang Magrib film regarding the tradition of pasung on people with mental disorders using Charles Sanders Pierce theory. The type of research used is descriptive qualitative with content analysis method to analyze the visuals and identify the meanings that appear in the film. This research uses Charles Sanders Pierce's semiotic theory through aspects of icons, symbols, and indexes that focus on the tradition of pasung on people with mental disorders experienced by Nina. The object of this research is the movie